Peran Semantis Pronomina dalam Bahasa Mandar - Jerniati I (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2014)
This research analysed the semantics role of pronoun in Mandarese from structural morphology perspective. This research aims to describe semantics role of pronoun in Mandarese. It used descriptive qualitative method, data collecting by elicitation technique, recording and noting, and documentation analysis.Oral data were gained from native speakers and writing data were got from Mandarese folkloreand relevant researchs. The analysis of reality showed three semantics roles that can be functioned by pronoun in Mandarese sentences, namely (1) agentif role in forms of free, active, and passive, (2) goals role, dan (3) locative role.